Revision of infected knee arthroplasties in Denmark. (3rd July 2016) - Lindberg-Larsen, Martin; Jørgensen, Christoffer C; Bagger, Jens; Schrøder, Henrik M; Kehlet, Henrik
Abstract : Background and purpose — The surgical treatment of periprosthetic knee infection is generally either a partial revision procedure (open debridement and exchange of the tibial insert) or a 2-stage exchange arthroplasty procedure. We describe the failure rates of these procedures on a nationwide basis. Patients and methods — 105 partial revisions (100 patients) and 215 potential 2-stage revision procedures (205 patients) performed due to infection from July 1, 2011 to June 30, 2013 were identified from the Danish Knee Arthroplasty Register (DKR). Failure was defined as surgically related death ≤ 90 days postoperatively, re-revision due to infection, or not reaching the second stage for a planned 2-stage procedure within a median follow-up period of 3.2 (2.2–4.2) years. Results — The failure rate of the partial revisions was 43%. 71 of the partial revisions (67%) were revisions of a primary prosthesis with a re-revision rate due to infection of 34%, as compared to 55% in revisions of a revision prosthesis (p = 0.05). The failure rate of the 2-stage revisions was 30%. Median time interval between stages was 84 (9–597) days. 117 (54%) of the 2-stage revisions were revisions of a primary prosthesis with a re-revision rate due to infection of 21%, as compared to 29% in revisions of a previously revised prosthesis (p = 0.1). Overall postoperative mortality was 0.6% in high-volume centers (> 30 procedures within 2 years) as opposed to 7% in the remaining centers (p = 0.003). Interpretation — The failure rates of 43% after the partial revision procedures and 30% after the 2-stage revisions in combination with the higher mortality outside high-volume centers call for centralization and reconsideration of surgical strategies.